Neurotoxic Effect of Cassava Cyanide on the Motor Activity and Cytoarchitecture of the Cerebellar Cortex of Albino Rats - Isaac John Umaru; Tyem Lawal Danjuma; Katchim Evelyn Shadrach; Julius Ishaya Salman; Jibaniya Grace Mchibuma; Kerenhappuch Isaac Umaru (African Journal of Biochemistry and Molecular Biology Research, 2026)
Cassava (Manihot esculenta Crantz), a widely consumed staple in tropical regions, contains cyanogenic glycosides that release hydrogen cyanide (HCN) upon hydrolysis. Chronic exposure to cassava-derived cyanide has been implicated in neurodegenerative disorders, particularly affecting motor coordination and cerebellar function. This study investigates the neurotoxic effects of cassava cyanide on motor activity and cerebellar cytoarchitecture in albino Wistar rats. Thirty adult male rats were divided into three groups: control, low-dose cyanide (10 mg/kg), and high-dose cyanide (20 mg/kg), administered orally for 15 days. Motor performance was assessed using rotarod and open field tests, while cerebellar tissues were examined histologically using hematoxylin and eosin staining. Results revealed a dose-dependent decline in motor coordination and locomotor activity, with significant reductions in rotarod latency and open field distance in cyanide-treated groups compared to controls (p < 0.05). Histological analysis showed progressive Purkinje cell degeneration, vacuolation, and disrupted laminar architecture in the cerebellar cortex, particularly in the high-dose group. These findings suggest that cassava cyanide exerts neurotoxic effects on cerebellar neurons, impairing motor function through structural damage. The study underscores the importance of safe cassava processing and dietary interventions to mitigate cyanide-induced neurotoxicity in vulnerable populations.